ASSESSMENT OF THE TECHNICAL STATE OF TIMBER OUTLET ELEMENTS OF UNDERGROUND SUPERSTRUCTURES WHILE HOLDING THE MONITORING OF OPERATING UNDERGROUND RUNNING LINE TUNNELS IN MINSK - Pastushkov, V. G.; Kastsiukovich, V. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Timber elements computation methods are presented in the article including the endurance of load action and humidity for timber strength in accordance with statutory documents. The analysis of humidity and temperature conditions of the underground constructions is performed; defects and damages, timber outlet elements of underground superstructure of normal operating are described in details. An alternative method of timber elements underground superstructure longevity rising is proposed in obedience to the mentioned reasons of the decreasing longevity.
Keywords: transportation construction; longevity; reliability; defects; damages; sleepers; tunnels; monitoring; deformations